2014
DOI: 10.1093/jnci/dju162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of miR-142-3p on the M2 Macrophage and Therapeutic Efficacy Against Murine Glioblastoma

Abstract: These data indicate a unique role of miR-142-3p in glioma immunity by modulating M2 macrophages through the transforming growth factor beta signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 36 publications
2
87
0
Order By: Relevance
“…1E). The change of cell morphology is an approach widely used to assess the phenotype of macrophages (10,(21)(22)(23)(24). Specifically, Su et al (10) showed that macrophages that are polarized to M2-like TAMs by cancer cell-derived lactate exhibit stretched and elongated morphology.…”
Section: Resultsmentioning
confidence: 99%
“…1E). The change of cell morphology is an approach widely used to assess the phenotype of macrophages (10,(21)(22)(23)(24). Specifically, Su et al (10) showed that macrophages that are polarized to M2-like TAMs by cancer cell-derived lactate exhibit stretched and elongated morphology.…”
Section: Resultsmentioning
confidence: 99%
“…miR-142-3p has been reported to be downregulated in diverse types of cancer, including leukemia, thyroid follicular carcinomas, cervical cancer, hepatic cancer, glioblastoma, osteosarcoma and non-small cell lung cancer (16)(17)(18)(19)(20)(21)(22). miR-142-3p has been demonstrated to contribute to carcinogenesis by regulating cell cycle, cell migration, apoptosis and invasion by targeting various signaling pathways and…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies emphasized that manipulation of miRNAs and their oligonucleotide antagonists, including miRNA-based nanodrugs, miRNA mimics, miRNA sponge and miR-mask, represents an attractive approach for antitumor therapy (12,13). In the GBM model, miRNAs could modulate pivotal protein expressions in the signaling cascades, thus, regulate tumor malignant behaviors (14)(15)(16). We propose that by overlapping the datasets of predictive miRNAs targeting CXCR4 and the miRNA profiling between GBM tissues and adjacent normal tissues, we could identify the tumor-specific miRNAs regulating CXCR4 expression in GBMs and offer new miRNA candidates for anti-GBM strategies.…”
Section: Introductionmentioning
confidence: 99%